Extra dimensions in superstring theory - Berkovits, Nathan [UNESP] (Elsevier, 1997)
It was earlier shown that an SO(9,1) θα spinor variable can be constructed from RNS matter and ghost fields. θα has a bosonic world-sheet super-partner λα which plays the role of a twistor variable, satisfying λΓμ λ = ∂xμ + iθΓμ ∂θ. For Type IIA superstrings, the left-moving [θL α, λL α] and right-moving [θRα, λRα] can be combined into 32-component SO(10,1) spinors [θA, λA]. This suggests that λAΓAB 11 λB = 2λL αλRα can be interpreted as momentum in the eleventh direction. Evidence for this interpretation comes from the zero-momentum vertex operators of the Type IIA superstring and from consideration of DD-branes. As in the work of Bars, one finds an SO(10,2) structure for the Type IIA superstring and an SO(9, 1) × SO(2, 1) structure for the Type IIB superstring. © 1997 Elsevier Science B.V.